2011
DOI: 10.1007/s00330-011-2161-z
|View full text |Cite
|
Sign up to set email alerts
|

Focal nodular hyperplasia-like lesions in patients with cavernous transformation of the portal vein: prevalence, MR findings and natural history

Abstract: FNH-like lesions are commonly detected in patients with CTPV. Most lesions demonstrate benign imaging findings and stable clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 33 publications
2
38
2
1
Order By: Relevance
“…In their series, only one fatcontaining HCA was detected on pathology. (2) In the present case, an association of FNH, multiacinar regenerative nodules, and HNF1A mutated HCC was demonstrated. During follow-up, the progression and malignant transformation into HCC HNF1A inactivated was demonstrated.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In their series, only one fatcontaining HCA was detected on pathology. (2) In the present case, an association of FNH, multiacinar regenerative nodules, and HNF1A mutated HCC was demonstrated. During follow-up, the progression and malignant transformation into HCC HNF1A inactivated was demonstrated.…”
Section: Discussionsupporting
confidence: 56%
“…CTPV markedly alters hepatic vascular hemodynamics and may result in growth of hypervascular regenerative nodules. Marin et al observed so‐called FNH‐like lesions in 12 of 58 patients (21%) with CTPV . They postulated that these so‐called FNH‐like lesions represent a regenerative hyperplasia of the hepatic parenchyma in response to increased arterial perfusion in areas with decreased portal blood flow.…”
Section: Discussionmentioning
confidence: 61%
“…[6][7][8] They have been described in Budd-Chiari syndrome and other vascular liver disorders. 2,9,10 An increased incidence in long time cancer survivors previously treated by chemo or radiotherapy, especially paediatric patients, has also been described, and the mechanism seems to be related to the non-selective effect of chemotherapy regimens in the non-tumorous liver. [11][12][13] Particularly, the use of oxaliplatin-based compounds has been associated with such FNH-like lesions.…”
Section: Introductionmentioning
confidence: 99%
“…18 Other differences have been reported, such as T1 hyperintensity and T2 hypointensity of MRN lesions, absence of the central scar or a hypodense/intense rim. 2,9,17,19 Furthermore, MRN should be differentiated from malignant liver lesions, especially metastases in the case of follow up of oncologic patients. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…According to published clinical and pathological studies, the prevalence of hepatic cyst and hemangioma in the general population ranges from 0.06 to 17.8% and from 0.1 to 20%, respectively [4,5,6,7]. Focal nodular hyperplasia (FNH) and hepatic adenoma are less frequent (0.2-3.2% and 0.04-1.5%, respectively) [8,9,10]. Autopsy series have reported a high prevalence of benign focal liver lesions of 52% in patients with no known history of a malignant tumor [11].…”
Section: Introductionmentioning
confidence: 99%